Analisis Pengaruh Kerahasiaan Informasi Pribadi Dan Keamanan Situs Internet Terhadap Kepercayaan Bertransaksi Online - Hapsari, Dewi Sri Wahyu; , Ihwan Susila, SE., M.Si., Ph.D (2016)
This study aimed to analyze the influence of the privacy and security of personal information on the internet sites of confidence to transact online. The sample used in this study were 120 respondents and objects taken on social media user respondents who never conduct online ransactions. In this study using a test instrument data, and classical assumption. The results showed the confidentiality of personal information and the security of internet sites significantly influence the confidence to transact online. The results of the study can be useful for managing online transaction services to provide the best service for customers. Keywords: Privacy, Security and Trust Online Transaction.